A Prospective Clinical Study for Safety and Efficacy of Intralesional Tuberculin Purified Protein Derivative in Treatment of Palmoplantar Verruca - Mishra, Aditi; Shrestha, Smriti; K.C., Shekhar; Karn, Dharmendra (Journal of Nobel Medical College, 2022)
Background: Multiple treatment options are available for verruca, however none is completely effective. Conventional modalities such as salicylic acid, cryotherapy have inconsistent treatment efficacies. Newer modalities such as immunotherapy, bleomycin and lasers have shown higher clearance rates of warts in recent studies. Immunotherapy is an innovative approach to treat warts which relies on the principle of enhancement of cell-mediated immunity. This study was done to evaluate the efficacy of immunotherapy with Tuberculin Purified Protein Derivative injection in palmoplantar verruca in our context. Materials and Methods: This is an open labelled, prospective interventional study. Patients with palmoplantar verruca enrolled in the study were injected with purified protein derivative intralesionally by an insulin syringe at a dose of 10 IU (0.1 mL) in the largest wart every 2 weeks until all lesions disappeared or for a maximum of six sessions. They were followed up for 3 months after final treatment session. Results: A total of 54 patients, 34 males and 20 females, were enrolled in the study. Commonest distribution of palmoplantar verruca was in plantar distribution (48.1%). Among them, 12 (22.2%) patients had periungual warts. Complete clearance of warts without any scarring was seen in 66.7% (36) patients with palmoplantar verruca at the end of 6th session whereas 33.3% (18) patients did not respond. Adverse effects noted were erythema, edema and pain at injection site. Conclusion: Intralesional injection of purified protein derivative is an effective and inexpensive treatment option for palmo-plantar verruca with good outcome.